Evaluation of cytotoxic and genotoxic effects of Microcystin-LR in Saccharomyces cerevisiae - Barreiros, Sara (2017)
Microcystins (MC) are hepatotoxins produced by cyanobacteria. Among the MCs, the microcystin-LR (MC-LR), produced by several cyanobacterial species, especially by the species Microcystis aeruginosa, is the most abundant and also the most well studied cyanotoxin. MCs are cyclic peptides which have high affinity for protein phosphatases Serine/Threonine (PPs), namely PP1 and PP2A, thus acting as their inhibitors, especially of the last one. It is from these interactions that a series of events occur which are responsible for the MCs cytotoxic and genotoxic effects on animal cells. It is also known that MCs induce oxidative stress in cells due to the production of reactive oxygen species (ROS), however a complete characterization of the effects of these toxins has not yet been obtained. This project intends to clarify some of the molecular mechanisms of MC-LR toxicity in animal cells using Saccharomyces cerevisiae as an eukaryotic organism model. To evaluate the cytotoxic effects of MC-LR, a cell viability assay was used to determine the functional capacity of the mitochondria, the MTT assay, after exposing the yeasts to different concentrations of MC-LR for 4 hours. Genotoxic effects were evaluated by gene expression studies for genes Rad27, Apn1, Apn2, Ntg1 and Ntg2 (from the BER DNA repair system) and Cdc55 gene which encodes the PP2A phosphatase protein, using the Real-Time qPCR technique. The reference genes used for expression normalization were Alg9 and Taf10. Furthermore, it was attempted to adapt the single cell gel electrophoresis assay (comet assay), conventionally performed on mammalian cells, to Saccharomyces cerevisiae cells, in order to quantify induced DNA breaks. MTT was optimized and successfully used in S. cerevisiae. Apparently, MC-LR is not cytotoxic for Saccharomyces cerevisiae, although these results should be confirmed with other methods that accessed cell viability. Regarding the Comet assay, the results were not conclusive, possibly due to the difficulty in optimizing the method when applied to yeast cells, particularly in the DNA migration on the electric field. However, the first two steps of the YCA protocol were optimized. Concerning the RTqPCR method it was possible to obtain tendencies in the gene expression levels, when compared with the control situation, thus revealing that MC-LR affects differently both BER pathways. Despite the difficulty of reproducing some methods in yeast cells, it appears that microcystin- LR plays a critical role in the toxicity of eukaryotic cells. This work allowed us to contribute with a little more information to a still relative unknown study field.